2017
DOI: 10.1097/hjh.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid 2 function regulates cardiac hypertrophy via stretch-induced activation

Abstract: We conclude that TRPV2 function, as a stretch-activated channel, regulates the development of cardiomyocyte hypertrophy in response to increased afterload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…The Hsp20-S10F PPCM model also had significantly increased mRNA levels of ANP, consistent with the development of pathological hypertrophy. Additionally, TRPV2 has been found by our laboratory, as well as others, to be a stretch activated channel that increases expression under stress/stretch conditions [47,48]. In this model, we found that TRPV2 expression did not change in WT mice, but was significantly higher in untreated Hsp20-S10F mice in comparison to the treated which is consistent with the observed LV remodeling in the untreated mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Hsp20-S10F PPCM model also had significantly increased mRNA levels of ANP, consistent with the development of pathological hypertrophy. Additionally, TRPV2 has been found by our laboratory, as well as others, to be a stretch activated channel that increases expression under stress/stretch conditions [47,48]. In this model, we found that TRPV2 expression did not change in WT mice, but was significantly higher in untreated Hsp20-S10F mice in comparison to the treated which is consistent with the observed LV remodeling in the untreated mice.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are still of course preliminary. Further, the generalizability of the TRPV2 findings to human population will require further study since even though our data in animals demonstrated increased TRPV2 expression in response to stress [47], some researchers have reported decreased TRPV2 expression in human subjects with heart failure [50], while others have found no difference [51].…”
Section: Discussionmentioning
confidence: 79%
“…TRPV2 has been shown to play a role in Ca 2+ -induced myocyte degeneration in dilated cardiomyopathy [178]. A knockout of TRPV2 protects hearts against pressure-overload-induced hypertrophy, but produces no protection against AngII or β-adrenergic activation-induced hypertrophy, indicating that TRPV2 regulates cardiac hypertrophy through stretch activation [179]. A knockout of TRPV2 in mice also reduces age-related fibrosis and hypertrophy [210].…”
Section: Trpv2 and Cardiac Fibrosismentioning
confidence: 99%
“…14 Iwata et al initially described that cardiac-specific overexpression of TRPV2 resulted in chamber dilation of all cavities of the murine heart, 15 while our laboratory recently demonstrated increased expression of TRPV2 in diseased hearts. 16 Related studies by our laboratory demonstrated that stimulation of the channel with probenecid in isolated cardiomyocytes resulted in increased cytosolic calcium concentrations with improved contractility and relaxation, independently of the b-adrenergic signaling pathway. 17 Further translational studies in healthy and infarcted mice confirmed that probenecid results in improved inotropy and lusitropy in a dose-dependent manner and does not induce malignant arrhythmias or apoptosis.…”
mentioning
confidence: 94%
“…Expression of the transient receptor potential vanilloid 2 (TRPV2) channel was noted in abundance in murine myocardial tissue, specifically in the left ventricle 14. Iwata et al initially described that cardiac‐specific overexpression of TRPV2 resulted in chamber dilation of all cavities of the murine heart,15 while our laboratory recently demonstrated increased expression of TRPV2 in diseased hearts 16. Related studies by our laboratory demonstrated that stimulation of the channel with probenecid in isolated cardiomyocytes resulted in increased cytosolic calcium concentrations with improved contractility and relaxation, independently of the β‐adrenergic signaling pathway 17.…”
Section: Introductionmentioning
confidence: 99%